The link among innovation drivers, green innovation and business performance: empirical evidence from a developing economy. (2016) - Singh, Manvendra Pratap; Chakraborty, Arpita; Roy, Mousumi
In recent years, growing attention among consumers, government and community towards environmental health has given importance to green innovation among industrial sector in developing economies. However, little research has been devoted to the consideration of the relation among innovation drivers, green innovation and business performance in manufacturing micro, small and medium enterprises (MSME). This study aims to provide empirical evidences of green innovation to motivate manufacturing MSMEs toward environmentally responsible activities. The research findings strongly validate the influence of innovation drivers and green innovation with 61% variance explained for firm's business performance. Furthermore, it has been found that green process and green organisational innovation have significant impact on business performance as compared to green product innovation. These research findings will provide a strong platform for designing strategic plans and spur adoption of green innovation in MSMEs of developing economies.